PENGARUH FRAUD DIAMOND TERHADAP TENDENSI KECURANGAN PADA DRIVER GRABCAR - Nina Dayu Lutfiyanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Transportation companies that use online application in their operation have grown rapidly; one of which is Grab, regardless the fact that there are problems, e.g. fraud by drivers, in the business. The purpose of this explanatory research is 1) to predict and explain the effect of pressure on the tendency of fraud in GrabCar, 2) to predict and explain the effect of opportunity on the tendency of fraud in GrabCar, 3) to predict and explain the effect of rationalization on the tendency of fraud in GrabCar, 4) to predict and explain the effect of capability on the tendency of fraud in GrabCar. The population of this quantitative study is all GrabCar drivers, from which 30 samples were selected. The results show that 1) pressure, opportunity, and performance are in high or good category, 2) pressure, opportunity, rationalization, and ability positively and significantly influence the drivers’ tendency of fraud, and 3) pressure has a more dominant influence on drivers’ tendency of fraud than work motivation, which indicates that high pressure on drivers has a higher influence than work motivation in improving their performance. Keywords: Fraud diamond, Potential Cheating, GrabCar